KEPUASAN PERNIKAHAN DITINJAU DARI KETERAMPILAN KOMUNIKASI INTERPERSONAL - Muslimah, Alfiana Indah (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2014)
Marriage in Indonesia is the only legally recognized relationship between a man and a woman to express their sexual needs, economic, childcare, and to divide the roles between the couple. The importance of marriage makes people crave for a satisfying marriage. Marital satisfaction is determined by the extent to which the couple can feel the satisfaction of marriage, with matching each other?s physical, economic, emotional, and psychological needs. Marital satisfactionn itself can be defined as a feeling of pleasure in a marriage in those husband and wife relationship. A satisfying marriage is also characterized by intimacy, commitment, friendship, affection, sexual gratification, economic security, and opportunity for emotional growth. Marital satisfaction plays an important role in the sustainability of the marriage itself. Marital satisfaction makes the marriage last longer and reduce the possibility of the broke of the marriage (divorce). One of the factor that affect marital satisfaction is interpersonal communication. The design of the study is correlational study. Sampling method using purposive sampling (samples intended) with 32 samples. Data collection techniques uses a scale of interpersonal communication and marital satisfaction scale. The product moment correlation analysis using SPSS for Windows 16.0 (Statistics for Social Science). The result shows that correlation coefficient is 0.972. The results of statistical tests show that the probability of 0.00 (p <0.05), which means that there is a strong relationship between interpersonal communication anxiety and marital satisfaction.